FINANCIAL LITERACY AND PERFORMANCE OF MICRO, SMALL AND MEDIUM ENTERPRISES: A LITERATURE REVIEW - Imelfina Musthafa; Hefrizal Handra; Nasri Bachtiar; Werry Darta Taifur; Edi Ariyanto (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
This research aims to examine various articles regarding the influence of financial literacy on the performance of MSMEs. The literature used in this research comes from indexed journal databases searching for the keywords "financial literacy" and "performance". This research found various factors involved in measuring the influence of financial literacy on MSME performance consists of: dimensions of financial literacy, namely: knowledge, attitudes and behavior; factors that influence financial literacy are age, gender, education, length of work and income; strategies to increase financial literacy through training; MSME performance are: financial and non-financial performance. The impact of financial literacy on MSME performance is influenced by many factors. This research provides input for policy makers to increase the level of financial literacy of MSME business actors so that MSME performance becomes better, competitive and has a competitive advantage.